AB0282 Vitamin D Status in Patients with Rheumatoid Arthritis in Egypt. (10th June 2014) - Gamal, R.M.; Gaber, W.; Sayed, S.
Abstract : Background: Vitamin D is a regulator of calcium homeostasis.Vitamin D also plays a role in the function of the immune system.The immunomodulatory effects of vitamin D have been subject to extensive examination, leading to recent speculation that it may play a role in inflammatory diseases including rheumatoid arthritis (RA) Objectives: The aim is to estimate the prevalence of vitamin D deficiency in egyptian patients with RA & to analyze the association between 25-hydroxyvitamin D (25(OH)D with disease activity Methods: 55 patients and 25 controls were included. Serum 25(OH)D was measured. Disease Activity Score (DAS28) and Health Assessment Questionnaire (HAQ) were assessed. Patients were divided into 4 subgroups according to activity: High (DAS28 >5.1), Moderate (3.2 < DAS28 ≤5.1), Low (2.6≤DAS28≤3.2) and Remission (DAS28<2.60). Associations between levels of 25(OH)D and age, disease duration and activity were assessed Results: 25(OH)D deficiency, insufficiency & sufficiency were found in 16%, 4% & 80% of controls while 25(O H)D insufficiency & sufficiency were found in 21.8% &78.2%of RA patients with no significance difference between groups. According to DAS28 scoring, 9.1%, 7.3%, 63.6%, 20% of patients showed remission, low, moderate &high disease activity consecutively. Morning stiffness, swollen joints count and 25(OH)D levels were higher in patients with moderate disease activity versus those with remission. A negative correlation was found in RA patients between 25(OH)D & ESR Conclusions: In Egyptian RA patient's vitamin D deficiency is quite common, but similar to that found in control subjects; disease activity (expressed as ESR) is inversely related to 25(OH)D levels. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3744